Factor X Nagoya 1 and Nagoya 2: a CRM– Factor X Deficiency and a Dysfunctional CRM+ Factor X Deficiency Characterized by Substitution of Arg306 by Cys and of Gly366 by Ser, respectively - Miyata, Toshiyuki; Kojima, Tetsuhito; Suzuki, Kyoko; Umeyama, Hideaki; Yamazaki, Tomio; Kamiya, Tadashi; Toyoda, Hideki; Kato, Hisao (Thrombosis and Haemostasis, 1998)
We have identified, in two unrelated patients, factor X deficiency that we have designated factor X Nagoya 1 and Nagoya 2, respectively. The proband with factor X Nagoya 1 showed factor X activity level of 3% and factor X antigen level <10% of the normal control value. All the exons and intron/exon junctions of the factor X gene were studied using a strategy combining polymerase chain reaction (PCR) amplification and nonradioactive single-strand conformational polymorphism (SSCP) analysis. Exon 8 containing DNA fragment of the proband with factor X Nagoya 1 showed aberrant migration on SSCP analysis. All exon-containing DNA fragments amplified by PCR were sequenced, and we identified a C-to-T substitution in exon 8 in the human factor X gene of the proband, which results in the replacement of Arg306 by Cys. This genetic defect has been transmitted from her father, and her sister also carried the same mutation; both showed almost half the normal levels of both factor X activity and antigen. The coordinates of human factor Xa indicated that Arg306 in the catalytic domain is positioned at the beginning of the alpha-helix near the second EFG-like domain. The substitution for Arg of Cys has been supposed to cause the destruction of local alpha-helix formation, possibly leading to the secretion problem. The proband with dysfunctional factor X Nagoya 2 was characterized by factor X activity level of 34% with normal factor X antigen level of 80%. We identified one substitution of G for A in exon 8 in the human factor X gene of the proband, which results in the replacement of Gly366 by Ser. As the Gly366 is positioned at the primary substrate binding pocket, the replacement of Gly with Ser would cause a defect of substrate binding, leading to the loss of enzymatic activity.